1997
DOI: 10.1111/j.1399-6576.1997.tb04820.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro contracture test for diagnosis of malignant hyperthermia following the protocol of the European MH Group: Results of testing patients surviving fulminant MH and unrelated low‐risk subjects

Abstract: The IVCT for diagnosis of MH susceptibility in Europe has a high sensitivity and a satisfactory specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
154
0
22

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(179 citation statements)
references
References 21 publications
3
154
0
22
Order By: Relevance
“…[8][9][10] This does not compare favourably with a reported sensitivity of 97% to 99% for CHCT and in vitro contracture test (IVCT), respectively. 36,37 Published data indicate that the frequency of MH-causative RyR1 mutations is population-specific, with only a few mutations accounting for the majority of MH cases in some populations. 6 By comparison, we found that p.Arg614Cys, p.Gly341Arg, and p.Gly2434Arg are the most frequent mutations in the Canadian MHS population, accounting for almost 35% of mutation-positive families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] This does not compare favourably with a reported sensitivity of 97% to 99% for CHCT and in vitro contracture test (IVCT), respectively. 36,37 Published data indicate that the frequency of MH-causative RyR1 mutations is population-specific, with only a few mutations accounting for the majority of MH cases in some populations. 6 By comparison, we found that p.Arg614Cys, p.Gly341Arg, and p.Gly2434Arg are the most frequent mutations in the Canadian MHS population, accounting for almost 35% of mutation-positive families.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of RYR1 mutations in MHS individuals, together with the presence of discordant cases in families C-18 and C-27 and other MH families worldwide, 8,10 may be explained by the sensitivity and specificity of the CHCT, which identifies both false negatives and false positives at a low rate. 36,37,49 Another reason might be the possible involvement of as yet unrecognized genetic and environmental factors in the MHS phenotype. For example, mutations in calsequestrin (CASQ1) might be expected to cause MH, since a mouse CASQ1 knockout line displays MHS symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…If threshold concentrations of these ligands are exceeded, MH sensitivity is diagnosed. The European in vitro contracture test (IVCT) [45] and the North American caffeine-halothane contracture test (CHCT) [46] for MH status achieve high sensitivity (close to 99%) at the cost of reduced specificity (between 78 and 93%) [47,48]. Thus both false negative and false positive diagnoses will appear, leading to discordance and apparent lack of linkage, making it difficult to determine the genetic basis of MH in many families.…”
Section: T H E M O L E C U L a R B A S I S F O R M A L I G N A N T H mentioning
confidence: 99%
“…Four muscle bundles per patient were tested with the IVCT according to the European protocol and diagnosis of MHS or MHN was established. 2,3 Ryanodine contracture test The RCT was performed on fresh muscle bundles. Length and wet weight of each bundle was determined.…”
Section: In Vitro Contracture Testingmentioning
confidence: 99%
“…The ryanodine contracture test performed in addition to the IVCT may add clarity into diagnosing a patient as MH-susceptible or not. [1][2][3] Ryanodine, a plant alkaloid, causes time-and doserelated contractures of human skeletal muscle. It binds with high affinity to the ryanodine receptor protein (RYR1), a calcium channel at the sarcoplasmic reticulum.…”
mentioning
confidence: 99%